2022
DOI: 10.1177/09646639221115698
|View full text |Cite
|
Sign up to set email alerts
|

Echoes and Antibodies: Legal Veridiction and the Emergence of the Perpetual Hepatitis C Subject

Abstract: New drugs with the potential to cure hepatitis C have emerged. There is great optimism within medicine about the transformative potential of cure, but this overlooks the entrenched discrimination and stigma associated with both hepatitis C and injecting drug use and the role of law in re/producing it. Drawing on interviews with key stakeholders such as policymakers, lawyers, and representatives from peer organisations (N = 30), Latour’s (2013) work on legal veridiction, Fraser and Seear’s (2011) conceptualisat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…For instance, in other work, we have found that the effects of judgement and stigma can persist even post‐cure, with the lingering presence of antibodies sometimes interpreted as proof the person still ‘has’ the virus and is ‘infectious’, thus posing a ‘risk’ to others (Seear, Fraser, Mulcahy et al., in press ). We have also argued that biomedical imaginaries can help to generate and sustain stigma (Seear, Fraser, Mulcahy et al., in press ). That is, various forces and factors, including poverty and homelessness, shape access to treatment (Farrugia et al., 2022 ).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…For instance, in other work, we have found that the effects of judgement and stigma can persist even post‐cure, with the lingering presence of antibodies sometimes interpreted as proof the person still ‘has’ the virus and is ‘infectious’, thus posing a ‘risk’ to others (Seear, Fraser, Mulcahy et al., in press ). We have also argued that biomedical imaginaries can help to generate and sustain stigma (Seear, Fraser, Mulcahy et al., in press ). That is, various forces and factors, including poverty and homelessness, shape access to treatment (Farrugia et al., 2022 ).…”
Section: Discussionmentioning
confidence: 93%
“…Hepatitis C is enacted as a particular kind of problem, without distinction between those who were asymptomatic, had cleared the virus, had not known they had it and experienced severe symptoms. Importantly, as we have argued elsewhere, the Peters case demonstrates the law’s ‘potential to generate new harms by stigmatising all those with hepatitis C, those cured, and those at risk, even as [it] recognises the women infected with it as victims of a terrible wrong’ (Seear, Fraser, Mulcahy et al., in press ). It is important to acknowledge the constitutive work being done by the uncertainty of disease progression here, as well as anticipation or supposition: The mere anticipation of symptoms or side effects can be enough to render something serious.…”
Section: Hepatitis C In the Australian Criminal Lawmentioning
confidence: 90%
See 3 more Smart Citations